Prospecting Marine Natural Products as the Disease-Modifying Treatment of Alzheimer’s Diseases - Saputri, Legis Ocktaviana; Harahap, Herpan Syafii; Rivarti, Arina Windri; Zubaidi, Fitriannisa Faradina (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2024)
Alzheimer's disease (AD) is a severe and high costs health problem all over the world. To date, there is no therapy capable of curing AD, making drug discovery a challenging and intriguing field to explore. Targeting marine natural products (MNPs) as a source of drug leads is a suitable choice considering the content of bioactive compounds and promising pharmacological benefits. This article aims to look at MNPs with prospects in several prime targets in AD pathology to cure AD. Marine vertebrates (fishes), marine invertebrates (sponges, tunicates, ascidian, clams, scallops, sand dollars, crabs, cockle, sea cucumber, shrimp, bryozoa, marine worm), algae/seaweed, and marine microorganisms (marine fungi, bacterium, dinoflagellata, microalgae) can be potentially used as disease-modifying treatments (DMTs) for AD. By targeting multiple aspects of AD pathology, these MNPs offer a multifaceted approach to treating and potentially modifying the disease course. This result is an intriguing gap for researchers in the discovery and development of new drugs that can improve AD pathology.